Development of a model to support midwives experiencing adverse events in obstetric units of the Tshwane District, Gauteng Province - Morobe, Rebotile Violet (My University, 2024)
Background: The World Health Organisation has reported that Adverse Events (AEs) are announced daily internationally and nationally. An AE is an unintentional event that is and could be harmful to the patient, occurring during health care delivery. The United States of America was reported to have the highest AEs among developed countries. Although in SA ‘The Status of Women's Health’ indicated progress regarding the maternal mortality ratio that has decreased nationally from 105.9 deaths per 100,000 live births in 2019 to 88 deaths on media in 2020. The mission of the National Department of Health (NDoH) in South Africa (SA) is to improve the health status of the community, prevent ill health, deliver service, and ensure that adverse events (AEs) are decreased. From 2020 to 2021, 252 AEs occurred in three Gauteng district hospitals in the presence of midwives who were expected to carry on with their duties. Midwives in obstetric units were affected by the occurrence of AEs as they were blamed when AEs occurred. Once blamed, they were psychologically and emotionally affected, leading to poor delivery of care. Fear of being stripped of their professional status once found guilty by the South African Nursing Council (SANC) the professional body, as litigations are rife in the health profession. Social media pressure on nursing misconduct and negligence of patients in public hospitals added fear to the midwives, resulting in poor performance and lack of concentration when caring for patients. Midwives, once involved in AEs become psychologically and emotionally disturbed, and cannot deliver proper care to mothers as they face consequences, fearing loss of their professional status once criminal charges are laid or the regulatory body SANC finds them guilty. As such, this study was conducted to develop a model to support midwives after experiencing AEs in the Tshwane district, Gauteng province. The objectives of phase one that emerged from the qualitative strand were to describe challenges experienced by midwives related to AEs in obstetric units of the Tshwane district. Secondly, to explore the strategies used by managers in case of an AE in obstetric units. The quantitative objectives were to assess the support offered to midwives by their managers post AEs in obstetric units. Another strategy was to identify the factors influencing proper delivery of care by midwives to prevent AEs in obstetric units of the Tshwane district, Gauteng province. Methodology: A convergent parallel mixed-method research study design was used for this study which had three phases. Phase 1 utilized a Mixed Method Research (MMR) design which comprised qualitative and quantitative data collection and analysis. The population used in this phase were Midwives, line and Operational managers. Purposive and simple random sampling was used to recruit participants. Selected participants had to have more than two years of experience in the obstetric unit, and know or experienced the studied phenomenon. The quantitative strand made use of the Slovin formula, sample size was calculated by the statistician. Ethical Clearance was obtained from the University of Limpopo Research Ethics Committee and the Tshwane District of Health selected facilities. Participants signed the consent form before data collection. Self-administered questionnaires for the quantitative 0approach and in-depth face-to-face interviews for the qualitative approach were used for data collection. The population size the for quantitative strand was 100, and the sampled number of midwives was 89. In the qualitative strand, data saturation was reached at 22 midwives. Managers were interviewed separately and a total of 12 managers were interviewed categorized as line managers and operational managers of the selected public district hospitals of Tshwane Gauteng province. A total of 34 qualitative interviews were conducted in the selected district hospitals of Tshwane, Gauteng province. Data analysis was analysed using Tesch’s open coding method for qualitative and Statistical Package for Social Sciences (SPSS) version 24 for the quantitative strand. Trustworthiness was adhered to, that is credibility, dependability, confirmability, and transferability. Phase 2: Concept analysis was selected as an appropriate method of choice followed in the model development, as defined by Walker and Avant (2005). This method involves examining the basic elements, structures of concepts, definitions, and functions of concepts, followed by the development of the model following the concepts, according to Chinn & Kramer (2018). Phase 3: Model validation, where the Nominal Group Technique (NGT) was used to validate the developed model according to Chinn and Kramer 2018. Experts in maternal health care services were sampled to validate the developed model for its importance, simplicity, applicability, and relevancy in supporting midwives who might experience AEs in maternal health care services. Recommendations: Raised recommendations were that operational and psychological support was vital for participants to cope with AEs. Flexible working hours were identified as a relief for strenuous long working hours and shortage of staff. Open lines of communication were suggested, and involvement in decision-making matters that involved participants rather than management taking decisions on their behalf. Equal treatment of participants and recognition where necessary and considered points of concern. Summary: This study focussed on raising facts on challenges faced by midwives in public hospitals exacerbated by a lack of support from management on both human and material resources. Lack of proper care gave rise to adverse events and financial litigations of the Health Department by the community. Shortage of staff added to the lack of support for midwives in providing care. Strategies were implemented by managers to provide support to midwives. Concepts were used to guide the development of a model used as a framework of reference. Recommendations were set to reach the optimum goal of care in the district hospitals of Tshwane.
Thesis (Ph.D. (Nursing Science)) -- University of Limpopo, 2024
Keywords: Adverse events; Midwife; Model validation; Model development; Obstetric Unit; Public hospital,; Support; Midwives; Maternity nursing; Public hospitals; Nursing care plans; Hospitals -- Maternity services